Analisis Putusan Pengadilan Agama No. 299/Pdt.G/2022/PA. PspK (Padang Sidempuan Kota) Tentang Isbat Nikah Poligami yang Masih Dalam Pernikahan yang Sah - Muthia Erina Nasution; Ali Akbar (UNES Law Review, 2023)
Basically, the confirmation of marriage isbat arising from a polygamy union cannot be approved, according to SEMA No. 3 of 2018. However, in Rulling No. 299/Pdt.G/2022/PA.PspK (Padang Sidempuan City), the judge decided to validate the confirmation of marriage from the polygamy union considering several aspects, namely that the marriage of the marriage of the Petitioner and the Respondent had fulfilled the requirements and essential elements of marriage according to Islamic law, and the judge considered the decision of Cassation Number 233/K/Ag/2020. His research aims to analyze the judge’s considerations in gratinting the petition for confirmation of marriage arising from a polygamy union. The study involves empirical juridical research using a qualitative approach.